Development of nanomaterial-supported molecularly imprinted polymer/receptor-like sensor for the detection of rosuvastatin from binary mixtures - Mahdi Gharibi; Ensar Piskin; Nadia Bounoua; Ahmet Cetinkaya; Sibel A. Ozkan (Talanta Open)
Statins reduce cholesterol synthesis by inhibiting the enzyme hydroxymethylglutaryl-CoA (HMG-CoA) reductase. Rosuvastatin (ROS) is a statin drug used to prevent cardiovascular diseases and treat abnormal lipids. This study describes the design and fabrication of a nanomaterial-assisted molecularly imprinted polymer (MIP)-based electrochemical sensor for ROS determination. In addition, MIP-based electrochemical sensors were designed to detect ROS in both standard solutions and serum samples. In the MIP-based electrochemical sensor developed via the photopolymerization (PP) technique on the glassy carbon electrode (GCE) surface, were used zinc oxide nanoparticles (ZnO NPs) as a pore former, p-aminobenzoic acid (p-ABA) as functional monomer, ROS as template molecule. Electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and scanning electron microscopy (SEM) techniques were used to carry out detailed characterizations concerning surface morphology and electrochemistry. Under optimized experimental conditions, the linearity range of the designed sensor was found 1.0 × 10−13–1.0 × 10−12 M. The superior selectivity of the MIP-based sensor against ROS in the presence of their binary mixtures was confirmed by interference studies. The recovery rates of the MIP-based sensors were calculated as 100.35 % and 99.16 % in commercial tablet form and serum samples, respectively. Moreover, the proposed sensor's relative selectivity coefficient (k′) was calculated, and it provided good selectivity for ROS over the NIP sensor. In conclusion, this newly developed sensor offers an advantageous approach for selective, sensitive, rapid and cost-effective analysis of ROS from binary mixtures. Additionally, this study is the first electrochemical sensor using nanomaterial-assisted MIP technology for ROS analysis, and its sensitivity is higher than that of other studies in the literature.